2021
DOI: 10.1007/s00415-021-10728-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain atrophy and cognitive impairment in Parkinson’s disease patients with and without probable rapid eye movement sleep behavior disorder

Abstract: Background The presence of rapid eye movement sleep behavior disorder (RBD) contributes to increase cognitive impairment and brain atrophy in Parkinson’s disease (PD), but the impact of sex is unclear. We aimed to investigate sex differences in cognition and brain atrophy in PD patients with and without probable RBD (pRBD). Methods Magnetic resonance imaging and cognition data were obtained for 274 participants from the Parkinson's Progression Marker Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
(47 reference statements)
4
23
2
Order By: Relevance
“…The increased GMV in the putamen in the PD patients with NCI was unexpected but was consistent with the previous studies [ 57 , 58 ], and may support the concept of striatum compensation in PD. The putamen is the striatal nucleus mainly linked with motor performance.…”
Section: Discussionsupporting
confidence: 91%
“…The increased GMV in the putamen in the PD patients with NCI was unexpected but was consistent with the previous studies [ 57 , 58 ], and may support the concept of striatum compensation in PD. The putamen is the striatal nucleus mainly linked with motor performance.…”
Section: Discussionsupporting
confidence: 91%
“…Male sex is risk factor for both iRBD and PD incidence, with around 80% of iRBD patients being male (Fernández‐Arcos et al, 2016) and the incidence of parkinsonism in males:females is 2:1 (Baldereschi et al, 2000). Oltra and colleagues (2022) explored the sex differences in disease incidence by stratifying the PPMI cohort. The authors found that male PD patients with RBD had greater global cortical atrophy and deep gray matter loss in the caudate, pallidum, and brainstem regions compared to female PD patients with RBD.…”
Section: Structural Imaging Abnormalitiesmentioning
confidence: 99%
“…Meta analyses identify male sex as a risk factor for cognitive and memory dysfunction in PD[3436]. Male patients are also more likely to develop cognitive and memory deficits early, to experience a more rapid course of cognitive decline and to be at greater risk for cognitive and memory deficits to progress to PDD[34, 37, 38]. These sex-specific features raise critical questions about the impacts of gonadal steroid hormones on cognition and memory in PD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, metaanalyses have identified male sex as conferring risk for cognitive and memory dysfunction in PD [34][35][36]. Clinical studies have also identified poorer spatial cognition, lower scores on tests of executive function, slower processing speed and reduced initiative in male compared to female patients as well as a greater likelihood for these deficits in males to progress from absent to mild and from mild to PDD [34,37,38]. These patterns suggest potentially important roles for circulating gonadal hormones in sex-specifically influencing cognition and memory in PD.…”
Section: Introductionmentioning
confidence: 99%